Interwoven Lives : Indigenous Mothers of Salish Coast Communities - Wellman, Candace (Book collections on Project MUSE., 2019)
"Interwoven Lives is a continuation of the Peace Weavers: Uniting the Salish Coast through Cross-Cultural Marriages. It adds four new biographies to the four published in Peace Weavers. Together the books offer a fresh look at the role indigenous women and their Euro-American husbands played in helping people of two colliding cultures live together in new communities"--